An evaluation of the program for executive development in a government bank - De Guia, Florencia
What most trainors in the Philippines commonly do at the end of the training program is to evaluate it according to participants' reactions gleaned fro. questionnaires given usually at the end of the program.The usual questions asked are : Did you like the training program? Was it relevant to your needs? Did you learn anything from it? Little however has been done about evaluating training programs in terms of changes in the on-the-job behavior of the participants and their results and effects on the organization, Hence, the comment that the "state of the art" of training evaluation is still in its infancy. This dissertation is a pioneering study on managerial training evaluation at behavior and esults levels. It is concerned with evaluating specifically the Program for Executive development (PED) conducted by the Development Academy of the Philippines (DAP for the Philippine National Bank (PNB). The purpose of this evaluation is mainly to determine the effect of the PED on managerial performance, productivity and mobility. The study considered the interactive influences of four major variables, namely: (1) management development, (2) personal characteristics, (3) organizational climate, and (4) external environment, which actually operate the context of a comprehensive managerial situation. The study employed a quasi-experimental design, the post-test control group, and inestigated the variables of managerial performance, productivity and mobility which were hypothesized as resulting from participation in the PEd. It would have been more reliable to compare the pre- and post training performance of the PED participants only but this ideal evaluation design was not initially conceived in the planning of the PED: hence, the lack of baseline data. In comparing both the experimental and control groups, or the PEDs and the non-PEDs, respectively, the indicators of managerial performance used were the four functions of management: planning, organizing, leading and controlling (POLC) which were also the four modules of the PED. These indicators were operationalized and data were derived through a survey that employed a questionnaire accomplished by both PEDs and non-PEDs who were matched on the basis of their positions, the class of their branches and the regions where they belonged. Responses to the POLC questionnaire were statistically analyzed and further clarified by six case studies. the indicators of rpoductivity used were the expected results of day-to day branch operations under the Bank's MBO program relative to deposits, loans released and collected, outstanding loans, past due accounts, expenses and income which were culled from records and documents. On the variable of mobility, a scoring system was devised to determine the post-training rate of promotion of each subject. The salient funding of the study support the consclusion that there are no significant differences between the PED and non-PED groups in the areas of managerial performance productivity and mobility. this unexpected and somewhat disturbing ressults should not, however, be taken unilaterally on its face since there are other interesting reslts influenced by intervening variables. For one thing, it appeared that rank dictated the level of managerial performance, i.e., the higher one's rank, the higher the managerial performance for both groups. Likewise, the organizational climate influenced managerial performance. It was found out that a highly supportive organizational climate fostered "high" managerial performance, a finding which was clearly established among the PEDs. Although the case studies confirmed the eneral finding that there were no significant differences between the two groups, exceptions were noted,particularly, that the educational background suchas an MBA could influence perfomance and that innovativeness could be affected by the lack of support from an immediate superior. Mobility ws significantly affected by rank and education (MBA or Law), especially among those who have undergone the PED. The training program was rated favorably by the participants who acknowledged especially the benefits of interpersonal relationships and of forging linkages with colleagues in the trade. In a ntshell, the findings indicate that training, or PED in this case, in itself and by itself, cannot be considered a principal and direct cause of improved managerial performance. The implication is quite clear that one's rank and organizational support, coupled with managerial training, engendered a high level of performance on the job. On the whole, the indicators used point to the conclusion that PED did not have as much impact as desired. There were, however, other eneficial result. Inangible values of the PED have been acknowledge by the participants themselves. This suggests that training has had some influence on them. However, organizational realities such as strict systems and procedures seemed to have affected their exercise of the management functions. As an effort in training evaluation, the dissertation inspires an attitude beyond a mere "act of faith" mental framework among practitioners of Human Resource Developments. Ensuing efforts at designing training programs should therefore consider the network of organizational variables, such as those identified in the study, in order to merit a viable evaluation farmework that will clearly point out relationships. To this end, the surrogate models drawn from alied discipline, such as cost-benefit analysis (Econmics) and human resource accounting (Financial Management), have to be effectively utilized. The dissertation point out an HRD-OD model that links training with the rest of the organizational components (i.e., training as a cause of technology-structures). Training should henceforth set the stage for. an active commitment on the part of the participant to create useful changes which would benefit the organization and all its members.